Psychosocial factors associated with the use of psychoactive substances in children and adolescents from Pereira, Colombia - Álvarez–López, Ángela María; Carmona-Valencia, Natalia Jeaneth; Pérez-Rendón, Ángela Liceth; Jaramillo-Roa, Adriana (Universidad y Salud, 2020)
Introduction: The use of psychoactive substances is a public health problem with a high prevalence in adolescents, which also affects the individual and social development of adults. Objective: To determine the psychosocial factors related to the use of psychoactive substances in children and adolescents of a public school from Pereira (Colombia). Materials and methods: A descriptive correlational study was conducted on 235 students of a public school, aged between 10 and 19 years, who completed an anonymous survey to examine the prevalence and psychosocial factors associated with the use of psychoactive substances. Results: Adequate parental supervision is a protective factor against psychoactive drug use (p <0.05) (OR <1). Schoolchildren are 6.5 times more likely to engage in drug use when they interact with psychoactive-drug user friends (OR = 6.555. 95% CI (3.147-13.653)). Those with family members who engage in this drug use have a 2.2 times higher possibility to use psychoactive substances (OR = 2.231. 95% CI (1.292-3.852)). Conclusions: The use of psychoactive substances shows a high prevalence in the participating schoolchildren and is mainly related to factors such as being in higher grades in their school and having either a family member or a friend who uses psychoactive substances.